O corpo-cronômetro As temporalidades do corpo na literatura brasileira - Scholz, Janek; Wrobel, Jasmin (Romanistik, 2023)
The studies presented in this volume examine the intertwining of corporeality and temporality in Brazilian literature from interdisciplinary perspectives. In some narratives, the texts make explicit the protagonism of the illness itself and the ambivalent relationship that is built up between sick or aging people and their former selves. In this context, different ways of excluding bodies that are no longer young or 'healthy' and are kept out of the public sphere are problematized. Silence and loneliness, but also the urgency of living to tell, are often the driving forces behind the narratives and poems studied.